2017
DOI: 10.1016/j.jvs.2016.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of aortic growth in uncomplicated type B aortic dissection from the Acute Dissection Stent Grafting or Best Medical Treatment (ADSORB) database

Abstract: The new imaging analysis of the ADSORB trial patients identified the number of vessels originating from the false lumen as an independent predictor of false lumen growth in uTBAD patients. Increasing age was a negative predictor of aortic growth. Our analysis may help to identify which uTBAD patients are at higher risk and should receive TEVAR or be monitored closely during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 31 publications
2
69
0
Order By: Relevance
“…Kamman et al reported that the number of vessels originating from the false lumen is an independent risk factor of false lumen growth in patients with type B aortic dissection. 21) On the other hand, no significant differences in freedom from aorta-related death and freedom from distal aortic reoperation were observed between the groups although the percentage of the patients with postoperative patent false lumen at the descending aorta was significantly higher in the young group. Therefore, our aggressive approach of extended aortic arch replacement at the time of the initial operation is acceptable.…”
Section: Discussionmentioning
confidence: 75%
“…Kamman et al reported that the number of vessels originating from the false lumen is an independent risk factor of false lumen growth in patients with type B aortic dissection. 21) On the other hand, no significant differences in freedom from aorta-related death and freedom from distal aortic reoperation were observed between the groups although the percentage of the patients with postoperative patent false lumen at the descending aorta was significantly higher in the young group. Therefore, our aggressive approach of extended aortic arch replacement at the time of the initial operation is acceptable.…”
Section: Discussionmentioning
confidence: 75%
“…However, in the previously reported studies providing predicting factors for adverse aortic remodeling and aneurysmal formation, the reproducibility of various morphologic assessments was not assessed. 4,5,[18][19][20][21][22][23][24][25][26][27][28][29] In the present study, we aimed to provide a comparison of the reproducibility of two-and three-dimensional morphologic measurement techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors are indications for surgical intervention. Recently reported predictive factors of aortic enlargement include the number of vessels originating from the false lumen [17] and the number of intercostal arteries [18]. However, the mechanism of aortic expansion in chronic aortic dissection remains unclear.…”
Section: Discussionmentioning
confidence: 99%